2007
DOI: 10.1111/j.1524-4725.2007.33060.x
|View full text |Cite
|
Sign up to set email alerts
|

Autologous Cultured Fibroblast Injection for Facial Contour Deformities: A Prospective, Placebo-Controlled, Phase III Clinical Trial

Abstract: Our results indicate that autologous fibroblast injections can safely and effectively produce improvements in rhytids, acne scars, and other dermal defects continuing for at least 12 months after injection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
51
0
7

Year Published

2009
2009
2019
2019

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 54 publications
(59 citation statements)
references
References 31 publications
(38 reference statements)
1
51
0
7
Order By: Relevance
“…29,30 Autologous fibroblasts allow for permanent engraftment. Use of autologous fibroblasts encapsulated in a scaffold would seem ideal.…”
Section: Tissue Engineering Of the Scarred Vocal Foldmentioning
confidence: 99%
“…29,30 Autologous fibroblasts allow for permanent engraftment. Use of autologous fibroblasts encapsulated in a scaffold would seem ideal.…”
Section: Tissue Engineering Of the Scarred Vocal Foldmentioning
confidence: 99%
“…Bu çalışma sonunda toplam hasta memnuniyeti ilk yıl %92 iken 3.-4. yıllarda %70 oranında saptanmıştır. Son yıllarda yapılan bir araştırmada ise OKF ile tedavi edilen hastaların skarlarında 9. ve 12. aylarda %75 ve %81 oranında düzelme saptanmış ve bunun en az 12 ay devam ettiği belirlenmiştir 10 . Watson ve ark'ları akne skarı bulunan 10 hastada OKF tedavisi ile 6. ay sonunda %60-100 arasında gelişme saptamışlar ve skar yüzeyinde %10-85 arasında küçülme belirlemişlerdir 11 .…”
Section: Discussionunclassified
“…Autologous human dermal fibroblasts obtained from behind the ear have been used to treat facial contour defects in a phase III clinical trial (Isolagen Inc, reorganized in 2009 to Fibrocell Science, Exton, PA, USA) (143). It was observed that autologous dermal fibroblasts were safe and produced improvement especially in the treatment of acne scars.…”
Section: Oral Autologous Grafts For Extra-oral Applicationsmentioning
confidence: 98%